Hubungan gaya hidup dengan gejala gastritis pada mahasiswa tingkat akhir - Putri, Revania Aprilia; Aryani, Atik; Widiyono, Widiyono (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Gastritis, or stomach ulcers, is an inflammation of the gastric mucosa caused by irritation and infection caused by continuous compression, resulting in abrasions and wounds. Students in the productive age group (15-25) are known to be more susceptible to gastritis due to their busy schedules, stress levels, poor diet, poor meal frequency, and poor food intake. Purpose: To determine the relationship between lifestyle and gastritis symptoms in final year students. Method: This descriptive correlative study used a cross-sectional design. The sampling technique used was proportional random sampling with a sample size of 142. Data analysis used a gamma statistical test with a questionnaire as the research instrument. Results: Most respondents' lifestyles were in the fairly good category, and their gastritis symptoms were in the moderate category. The gamma statistical test yielded a p-value of 0.001 < 0.05. Conclusion: There is a relationship between lifestyle and symptoms of gastritis in final year students.   Keywords: Gastritis Symptoms; Lifestyle; Students.   Pendahuluan: Gastritis atau penyakit maag merupakan peradangan dari mukosa lambung yang terjadi akibat iritasi dan infeksi karena proses peremasan yang terjadi secara terus- menerus sehingga lecet dan luka. Mahasiswa yang termasuk dalam kategori usia produktif dengan rentang 15-25 tahun diketahui lebih mudah untuk terkena penyakit gastritis karena memiliki aktivitas fisik yang padat dengan tingkat kesibukan, tingkat stress, pola makan yang kurang baiki, frekuensi makan, serta asupan makanan yang tidak baik. Tujuan: Untuk mengetahui hubungan gaya hidup dengan gejala gastritis pada mahasiswa tingkat akhir. Metode: Penelitian deskriptif korelatif dengan desain cross sectional. Teknik sampling yang digunakan yaitu proportional random sampling dengan jumlah sampel 142. Analisis data menggunakan uji statistic gamma dengan Instrument penelitian menggunakan kuesioner. Hasil: Sebagian besar gaya hidup responden dalam kategori cukup baik dan gejala gastritis dalam kategori sedang. Hasil uji statistic gamma didapatkan nilai p value sebesar 0.001< 0.05. Simpulan: Terdapat hubungan gaya hidup dengan gejala gastritis pada mahasiswa tingkat akhir.   Kata Kunci: Gastritis; Gaya Hidup; Gejala; Mahasiswa.